Tissue Programmed Hydrogels Functionalized with GDNF Improve Human Neural Grafts in Parkinson's Disease (Adv. Funct. Mater. 47/2021). (18th November 2021) - Hunt, Cameron P. J.; Penna, Vanessa; Gantner, Carlos W.; Moriarty, Niamh; Wang, Yi; Franks, Stephanie; Ermine, Charlotte M.; de Luzy, Isabelle R.; Pavan, Chiara; Long, Benjamin M.; Williams, Richard J.; Thompson, Lachlan H.; et al.
Abstract : Tissue Programmed Hydrogels In article number 2105301, David R. Nisbet, Clare L. Parish, and co‐workers show that encapsulating human stem cell‐derived dopamine progenitors within a neural tissue biomimetic hydrogel enhances their engraftment in an animal model of Parkinson's disease. The laminin‐based hydrogel, simultaneously sustains delivery of glial cell‐derived neurotrophic factor and increases dopamine neuron survival and their plasticity, and consequently the functional capacity of the graft to reverse motor deficits.